Personalized medicine and pharmacogenomics - Popović, Mitar; Jakšić, Marina (PONS - medicinski časopis, 2025)
Personalized medicine refers to any clinical approach that emphasizes the systematic use of preventive, diagnostic, and therapeutic interventions based on genomic and family history data to enhance health outcomes. In this sense, personalized treatment is frequently referred to as genomic medicine. Personalized medicine has several health strategies that rely on the identification of molecular-genetic markers, including molecular diagnosis, prognosis, and disease monitoring; predictive genetics and preventive medicine; pharmacogenomics; targeted molecular therapy, and gene-based therapy. This paper presents a summary of current pharmacogenomics findings, as well as the field’s expected future progress. Pharmacogenomics is the study of how the entire genome influences an individual’s response to a medicine. The clinical application of pharmacogenomics enables clinicians to predict a patient’s response to a specific therapy based on information obtained from genetic tests, and to select the appropriate drug, drug dose, and duration of therapy in order to achieve the best possible therapeutic response in the patient while minimizing unwanted side effects. This necessitates objective and evidence-based guidelines, as well as an adequate infrastructure for accessing pharmacogenomic data, such as via the patient’s electronic health record. Although medicine has always been essentially "personalized," or tailored to each patient, personalized medicine now employs cutting-edge technology and knowledge in the fields of molecular genetics and genomics, allowing for a greater degree of personalization and significant progress in clinical medicine.